2011
DOI: 10.1111/j.1538-7836.2011.04497.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased tissue factor pathway inhibitor activity is associated with myocardial infarction in young women: results from the RATIO study

Abstract: Summary. Background: The tissue factor pathway inhibitor (TFPI)/protein S anticoagulant system is a potent inhibitor of blood coagulation. TFPI and protein S are major determinants of thrombin generation (TG) tests determined at low tissue factor (TF) and at high TF concentrations in the presence of activated protein C (APC). Both TFPI and protein S protect against venous thrombosis, but the importance of the TFPI/protein S system in arterial thrombosis remains unclear. Objectives: To investigate the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
3
17
0
2
Order By: Relevance
“…The prolonged lag time in cases of the present study is in accordance with the observation in the MARK study, where lagtime was prolonged in the acute phase but also at later timepoints [3]. This prolongation may be due to release of TFPI from perturbed endothelium such as demonstrated in a recent case control study in young women with manifestations of arterial thrombosis (AMI or stroke) [10]. However, also other changes in the balance between pro- and anticoagulant proteins may be involved in the alterations in thrombin generation profile.…”
Section: Discussionsupporting
confidence: 92%
“…The prolonged lag time in cases of the present study is in accordance with the observation in the MARK study, where lagtime was prolonged in the acute phase but also at later timepoints [3]. This prolongation may be due to release of TFPI from perturbed endothelium such as demonstrated in a recent case control study in young women with manifestations of arterial thrombosis (AMI or stroke) [10]. However, also other changes in the balance between pro- and anticoagulant proteins may be involved in the alterations in thrombin generation profile.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings that decreased APC sensitivity is associated with CHD risk stand in contrast to another large study which found increased (rather than decreased) sensitivity to APC in young women with myocardial infarction. 19 However, since this was a retrospective case-control study the measurement of APC sensitivity was performed in prevalent cases and therefore it is uncertain whether the findings reflect a compensating mechanism for an increased procoagulant state associated with underlying arterial disease. The prospective design of the current study is better suited towards identification of risk factors preceding incident disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective case-control study of myocardial infarction in young women cases compared to controls showed a decrease (rather than the expected increase) in APC resistance using the thrombin generation-based APC resistance test. 19 On the other hand a positive association of APC resistance with severity of arterial disease was found using the classical APC resistance test. 20 EPT induces an acquired resistance to APC in women without genotypic FVL, increases resistance in those with FVL, and increases risk of VT in women with and without FVL.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations